Scleral Patch Graft to the Rescue – Managing an Overfiltering Bleb - Aditi Singh; Meena Gopinath Menon; Mithuna Pappuru (Delhi Journal of Ophthalmology, 2025)
Postoperative hypotony is a vision-threatening complication which can occur in myriad scenarios. Overfiltering bleb is one such cause of hypotony which can resolve many times with conservative management. In cases of over filteration due to scleral patch defect or full-thickness scleral tear a meticulous bleb exploration with the usage of patch graft is advocated. In this case report, we describe one such case of overfiltering bleb in the early postoperative period due to scleral flap defect and full-thickness scleral defect, successfully managed using a scleral patch graft and conjunctival repositioning.